Utilisation of water disinfecting kit by armed forces personnel: a cross sectional study - Verma, K. C.; Malhotra, V.; Ram, Babu (International Journal Of Community Medicine And Public Health, 2017)
Background: Prevention of water-borne diseases is important for health and training of Armed Forces (AF) personnel. Although, supply of safe water is being ensured to them in military stations, but their training and frequent travels expose them to situations where water may be contaminated. To ensure prevention of water borne diseases, AF personnel are issued ‘Out-Fit Water Sterilising kit’- a kit containing halogen and chlorine-removing tablets. The present study aims to identify the knowledge-use gap in utilization of this kit by AF personnel. Methods: A cross sectional study among 649 randomly selected AF personnel was carried out in a large military station to identify the knowledge and practices of AF personnel regarding ‘OFWS kit’. The data was collected on structured questionnaire through face-to-face interview, and analyse using SPSS ver 20. Results: The study revealed progressive downward graph from knowledge regarding ‘OFWS kit’ (75.3%) to its availability (54.8%) and its ever-use (47.9%). Relevant service factors associated with use are presented. Conclusions: The study highlights the need to ensure regular training of AF personnel in use of ‘OFWS kit’, its availability at the grass-root level and supervision of its use to ensure positive health of Indian soldier always- a prerequisite for his optimal training.